2017
DOI: 10.18203/2349-3291.ijcp20170684
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal candidiasis: clinical spectrum and epidemiology in a tertiary care centre

Abstract: Background: Candidial infections are a serious problem in neonatal intensive care units (NICU) which increases the mortality and morbidity in addition to increasing health care costs. Confirming the diagnosis by laboratory tests is difficult and a high index of suspicion is required. The objective of this study was to identify the clinical spectrum and epidemiology of neonatal candidiasis in a tertiary care NICU.Methods: The present study was carried out in the NICU of SDM medical college and hospital, Dharwad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
4
2
0
Order By: Relevance
“…The results in this study showed that candidal sepsis commonly occurred in low weight and preterm neonates, similar results were reported in other studies by Schellack and Gous (32), Femitha and Joy (33), Kapila (34), and Koppad and Prakash (35). Low weight and preterm are risk factors for fungal sepsis because of immaturity of their immune system and invasive intervention.…”
Section: Discussionsupporting
confidence: 90%
“…The results in this study showed that candidal sepsis commonly occurred in low weight and preterm neonates, similar results were reported in other studies by Schellack and Gous (32), Femitha and Joy (33), Kapila (34), and Koppad and Prakash (35). Low weight and preterm are risk factors for fungal sepsis because of immaturity of their immune system and invasive intervention.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to studies from Pakistan, India and Italy which showed non-albicans Candida species as a cause of sepsis in neonates. 2,36,37 However, we found C. albicans to be associated with LOD along with the use of antibiotics as a significant risk factor, similar to other studies from India. 10,33,34 Despite high usage of carbapenems and cephalosporins in 2019 (60% and 53% in EOD and 73% and 57% in LOD, respectively) as compared with vancomycin (36% in EOD and 55% in LOD), the association of vancomycin with LOD was the only statistically significant finding.…”
Section: Discussionsupporting
confidence: 90%
“…20 Niranjan et al also demonstrated Candida krusei to be the predominant nonalbicans species followed by Candida tropicalis. 21 In this study we isolated C. parasilopsis and C. tropicalis amongst the second and third commonest species of nonalbicans Candida similar to studies done by Koppad et al 22 Although C. parasilopsis is less virulent, but because of indwelling catheters and high IV glucose infusion, the virulence may increase and is thus difficult to eradicate this organism. 23 All neonates with candidemia received antifungal treatment.…”
Section: Discussionsupporting
confidence: 78%